Mindfulness and job control as moderators of the relationship between demands and innovative work behaviours - Martín-Hernández, Pilar, (Colegio Oficial de Psicólogos de Madrid, 2020)
Innovation enables organizations to respond successfully to rapid changes in a business environment. This innovation capability largely relies on employees. Although workers are required to be innovative, their jobs frequently contain higher demands that might make it difficult for them to innovate at work. The Job Demands-Control model active hypothesis suggests that highly demanding jobs that allow individuals enough discretion enhance innovative performance. Improving an important attentional resource such as mindfulness at work might also play a similar role, although there is a need for more research at this level. The main aim of this study is to examine the relative contribution of job control and increases in mindfulness as moderators in the job demands-innovation work behaviours relationship. The results obtained with 221 workers indicated that in previous situations characterized by high job demands (T1), workers who increase their capacity for mindfulness are more innovative in the future (T2).